Case report: A CLCN1 complex variant mutation in exon 15 in a mixed-breed dog with hereditary myotonia - Eguchi, Gabriel Utida; Palumbo, Mariana Isa Poci; Cerri, Fabrício Moreira; Basso, Roberta Martins; Oliveira-Filho, José Paes de; Caramalac, Silvana Marques; Borges, Alexandre Secorun (Frontiers in Veterinary Science, 2024)
At 4 months of age, a male dog was presented with a complaint of a stiff gait following a startle response. Neurological examination revealed no deficits, but clinical myotonia was easily induced upon requesting the patient to jump. Additionally, myotonia of the upper lip muscles was observed upon manipulation. Hereditary myotonia was suspected, and electromyography confirmed the presence of myotonic potentials. Genetic testing of the myotonic patient identified a complex of mutations, including c.[1636_1639 delins AACGGG] and c.[1644 A>T], both located in exon 15 of the CLCN1 gene leading to the formation of a premature stop codon. Genetic investigations of the mother and four littermates revealed that, except for one littermate who was wild type, all others carried a copy of the mutated gene. To the best of the authors' knowledge, these mutations have not been previously reported.